Management of a rare presentation of Kindler disease with digital constriction bands—Case report. Issue 6 (6th September 2018) - Ting, Jeannette W. C.; Kaur, Sarbjit; Ogboli, Malobi; Irani, Kiri; Jester, Andrea
Abstract: Kindler disease is a type of epidermolysis bullosa associated with acral blistering, diffuse cutaneous atrophy, poikiloderma, mucosal stenosis, and photosensitivity. This is the first case report in the literature to describe constriction bands associated with Kindler disease causing ischemia of the fingertips requiring urgent release and full‐thickness skin grafts. Dermatologists reviewing such patients need to be aware of this condition and refer to a children's hand surgeon early to avoid leaving patients with prolonged periods of pain.